Tanzania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper analyzes trends in Tanzania's external competitiveness and export performance. Using various multilateral and bilateral real exchange rates, the paper looks at developments in Tanzania's real effective exchange rate since 1990. It evaluates the misalignment in the real exchange rate based on results from an equilibrium real exchange rate model that accounts for changes in the economic fundamentals. An analysis of other qualitative aspects of competitiveness is presented, and an assessment of public domestic debt evolution in Tanzania is also provided.